Pauses in breastfeeding babies and their relationship with the origin of verbal communication: a study with dizygotic twins - Gomez Ramos, Pablo (2020)
Human babies are the only mammals that pause in the process of breastfeeding during the first months of life, a unique fact that is not related to any practical use. In the 1980s, some researchers linked these pauses to formats of shift exchange between mother and child within a process equivalent to a dialogue or conversation. Using an intrasubject unifactorial and univariate design, we have made observations on a pair of dizygotic twins trying to check how widespread the stop in the sucking process is and what role adult intervention plays in such behaviours. The results show, on the one hand, that these are generalized behaviors and, on the other hand, that the intervention of the adult is not necessary, although it does condition them, which would reinforce the innate character of the pauses and also their possible relation with the origin of the language.